1999
DOI: 10.1093/ajcn/70.3.576s
|View full text |Cite
|
Sign up to set email alerts
|

Cyanocobalamin (vitamin B-12) status in Seventh-day Adventist ministers in Australia

Abstract: As part of the Adventist Ministers' Health Study, a series of cross-sectional surveys conducted in 1992, 1994, and 1997, the serum vitamin B-12 status of 340 Australian Seventh-day Adventist ministers was assessed in 1997. The ministers in the study participated voluntarily. Of this group, 245 were either lactoovovegetarians or vegans who were not taking vitamin B-12 supplements. Their mean vitamin B-12 concentration was 199 pmol/L (range: 58-538 pmol/L), 53% of whom had values below the reference range for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 2 publications
0
22
0
2
Order By: Relevance
“…In a cross-sectional survey [26], serum concentrations of vitamin B 12 that were lower than the normal value were observed in 73% of the vegetarian subjects who were not taking vitamin B 12 supplements. In this study [26], deficient vitamin B 12 intake was responsible for the low B 12 serum concentration in both LOV and vegans. Thus, it is reasonable to assume that our vegetarian subjects may have had high tHcy values because of their low vitamin B 12 intake.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a cross-sectional survey [26], serum concentrations of vitamin B 12 that were lower than the normal value were observed in 73% of the vegetarian subjects who were not taking vitamin B 12 supplements. In this study [26], deficient vitamin B 12 intake was responsible for the low B 12 serum concentration in both LOV and vegans. Thus, it is reasonable to assume that our vegetarian subjects may have had high tHcy values because of their low vitamin B 12 intake.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, it has been shown that vegetarians, and particularly vegans, have low blood levels of vitamin B 12 [25]. In a cross-sectional survey [26], serum concentrations of vitamin B 12 that were lower than the normal value were observed in 73% of the vegetarian subjects who were not taking vitamin B 12 supplements. In this study [26], deficient vitamin B 12 intake was responsible for the low B 12 serum concentration in both LOV and vegans.…”
Section: Discussionmentioning
confidence: 98%
“…Subnormal vitamin B-12 status is prevalent (50%–70%) in vegetarians or vegans in Austria Germany, Italy, Australia, India and China [45,46,47,48,49,50,51,52]. There has been some controversy about the definition of vitamin B-12 deficiency because of variability in clinical manifestation.…”
Section: Metabolic Vitamin B-12 Deficiency With Vegan or Related Dmentioning
confidence: 99%
“…This is similar to study conducted in Seventh-day Adventist ministers in Australia by Hokin BD et al in 245 vegetarians where serum level of vitamin B 12 below the reference range of study (126-627 pg/ml) was 53%. 14 The Marwari population have a high life style and standard of living comparable to Adventist minister of Australia. Similar reports of high prevalence of vitamin B 12 deficiency in vegetarians have been shown in different studies.…”
Section: Discussionmentioning
confidence: 99%